A preliminary evaluation of the impact of covid-19 on public transportation in Ibadan metropolis: a case study of Ibadan North local government (2020)
A number of measures have been put in place by different governments to combat the spread of Covid-19 virus. The virus has affected all forms of transportation. This paper is a preliminary study to evaluate the impact of Oyo State government lockdown measures on public transportation in Ibadan North Local Government Area between March and June 2020. Seven factors affecting public transportation as identified from literature include: availability of service, cost of service, comfortability safety /social distancing, parking difficulties and rate of accidents. Structured questionnaires were administered to purposively selected road users. The level of importance of each factor was determined and ranked by Relative Importance Index (RII). The study shows that there was a significant reduction in travel demand which in turn caused a significant increase in cost of transportation and waiting time for commuters.